Accounting for escape mortality in fisheries: implications for stock productivity and optimal management. Issue 1 (1st January 2014) - Baker, Matthew R.; Schindler, Daniel E.; Essington, Timothy E.; Hilborn, Ray
Abstract : Few studies have considered the management implications of mortality to target fish stocks caused by non‐retention in commercial harvest gear (escape mortality). We demonstrate the magnitude of this previously unquantified source of mortality and its implications for the population dynamics of exploited stocks, biological metrics, stock productivity, and optimal management. Non‐retention in commercial gillnet fisheries for Pacific salmon ( Oncorhynchus spp.) is common and often leads to delayed mortality in spawning populations. This represents losses, not only to fishery harvest, but also in future recruitment to exploited stocks. We estimated incidence of non‐retention in Alaskan gillnet fisheries for sockeye salmon ( O. nerka ) and found disentanglement injuries to be extensive and highly variable between years. Injuries related to non‐retention were noted in all spawning populations, and incidence of injury ranged from 6% to 44% of escaped salmon across nine river systems over five years. We also demonstrate that non‐retention rates strongly correlate with fishing effort. We applied maximum likelihood and Bayesian approaches to stock–recruitment analyses, discounting estimates of spawning salmon to account for fishery‐related mortality in escaped fish. Discounting spawning stock estimates as a function of annual fishing effort improved model fits to historical stock–recruitment data in most modeled systems. This suggests the productivity of exploited stocks has been systematically underestimated. It also suggests that indices of fishing effort may be used to predict escape mortality and correct for losses. Our results illustrate how explicitly accounting for collateral effects of fishery extraction may improve estimates of productivity and better inform management metrics derived from estimates of stock – recruitment analyses.